2017
DOI: 10.1007/s00464-017-5946-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical efficacies and safeties of lumen-apposing metal stent and conventional-type metal stent-assisted EUS-guided pancreatic wall-off necrosis drainage: a real-life experience in a tertiary hospital

Abstract: EUS-guided drainage of WON using FCSEMSs and LAMSs are comparable in efficacy and safety; however, the latter is associated with early stent revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…[15][16][17][18][19][20][21] Although LMAS was widely perceived superior to FCSEMS and PS, our study and some other latest studies revealed that efficacy and safety of LAMS might not be substantially improved, as suggested by the treatment outcomes compared with PS 17,22,23 and FCSEMS. 24,25 One possible reason was that metal stents with larger diameter allow the bidirectional movement of contents between the gastrointestinal tract and the cavity. Therefore, when the rapid drainage of PFC (especially for drainage of the WON contents) is facilitated, undigested solid material can also easily enter the cyst cavity and cause stent occlusion or cavity infection.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…[15][16][17][18][19][20][21] Although LMAS was widely perceived superior to FCSEMS and PS, our study and some other latest studies revealed that efficacy and safety of LAMS might not be substantially improved, as suggested by the treatment outcomes compared with PS 17,22,23 and FCSEMS. 24,25 One possible reason was that metal stents with larger diameter allow the bidirectional movement of contents between the gastrointestinal tract and the cavity. Therefore, when the rapid drainage of PFC (especially for drainage of the WON contents) is facilitated, undigested solid material can also easily enter the cyst cavity and cause stent occlusion or cavity infection.…”
Section: Discussioncontrasting
confidence: 45%
“…Although LMAS was widely perceived superior to FCSEMS and PS, our study and some other latest studies revealed that efficacy and safety of LAMS might not be substantially improved, as suggested by the treatment outcomes compared with PS and FCSEMS . One possible reason was that metal stents with larger diameter allow the bidirectional movement of contents between the gastrointestinal tract and the cavity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The included studies had been published between 2014 and 2019, with an enrollment period that ranged from 2005 to 2017 (Table ) . Among them, two were designed as a three‐arm study that compared efficacy among LAMS, DPPS, and FCSEMS .…”
Section: Resultsmentioning
confidence: 90%
“…In addition to studies comparing LAMS versus DPPS and FCSEMS versus DPPS, there are many studies on EUS‐guided PFC drainage comparing LAMS versus FCSEMS . These studies aimed to evaluate comparative efficacy between two types of stents in EUS‐guided PFC drainage; however, they resulted in only fragmented pairwise outcomes and could not provide comprehensive evidence including direct or indirect evidence for comparative efficacy among LAMS, DPPS, and FCSEMS.…”
Section: Introductionmentioning
confidence: 99%